Libco - Ahmad Khusaini, Noryana; Daud, Mohd Shamsul; Abd Rahman, Noraini; Nasrudin, Nur Hasni; Ahmad Junid, Rosida (Universiti Teknologi MARA, Kedah, 2019)
The emergence of Web 2.0 facilitates activities that are related to information storage and retrieval. However, the significance of the various web 2.0 tool available nowadays can go beyond its norms. This digital environment provides libraries a tool that enables them to reach out to societies with better prospects. Thus, this platform provides opportunities to all libraries to establish collaboration and partnership in strengthening their services to fulfill various types and needs of the users. LiBCO stands for “Library Portal for Community Outreach…” is a Web 2.0 Portal that is specially designed to unite all libraries in Malaysia to get closer to societies in a wider range of coverage. Libraries and community outreach programs will be emphasized in the development of this portal. There is a database system embedded in this portal that offers the visitors opportunities to involve and contribute to the outreach programs covered by all participated libraries in Malaysia.